2016
DOI: 10.1111/jgh.13340
|View full text |Cite
|
Sign up to set email alerts
|

Acute‐on‐chronic liver failure in India: The Indian National Association for Study of the Liver consortium experience

Abstract: Alcohol was the commonest etiology of ACLF. Within a mean hospital stay of 8 days, 42% patients died. OFs independently predicted survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 25 publications
(63 reference statements)
1
21
0
Order By: Relevance
“…42 Patients with CLD are at increased risk of severe HAV disease [13][14][15]17 and ACLF, which has a very high mortality rate. 16,29,32,44,45 Hence, such patients are recommended to receive various vaccinations, including HAV vaccination, in the US, 20 the UK, 21 and Sri Lanka. 75 Old studies from India showed a high seroprevalence of protective HAV antibodies among Indian adults with CLD, [25][26][27][28]30,31,[46][47][48] although the most recent ones (≤2007) found that nearly 7% of CLD patients did not have protective HAV antibodies and were therefore susceptible to HAV infection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…42 Patients with CLD are at increased risk of severe HAV disease [13][14][15]17 and ACLF, which has a very high mortality rate. 16,29,32,44,45 Hence, such patients are recommended to receive various vaccinations, including HAV vaccination, in the US, 20 the UK, 21 and Sri Lanka. 75 Old studies from India showed a high seroprevalence of protective HAV antibodies among Indian adults with CLD, [25][26][27][28]30,31,[46][47][48] although the most recent ones (≤2007) found that nearly 7% of CLD patients did not have protective HAV antibodies and were therefore susceptible to HAV infection.…”
Section: Discussionmentioning
confidence: 99%
“…32 In another retrospective study, which included 1049 consecutive patients with ACLF (mean age 44.7 ± 12.2 years; 81.3% male) conducted in 10 tertiary centers from across India during 2011-2014, the most common precipitants of ACLF were alcohol consumption (35.7%), viral superinfection/flare (HAV, HBV, or HEV) (21.4%), and sepsis (16.6%). 29 The underlying CLD was mainly alcohol (56.7%), cryptogenic (19.4%), or HBV/ HCV (15.9%). During a median (range) hospital stay of 8 (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) days, 42.6% of patients died.…”
Section: Aclfmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a recent study is significant as it seems to bring two definitions somewhat closer. On behalf of Indian Association for study of the liver (INASL) consortium for ACLF Research in the East or ICARE, Shalimar et al 31 have recently analyzed records of 1049 consecutive patients with ACLF satisfying APASL definition from 10 centers in India. They confirmed that mortality progressively increased with rising number of organ failures or OFs (12.3% with no OF and 83.3% with five OFs).…”
Section: Acute On Chronic Livermentioning
confidence: 99%